Who Gets What from International Organizations? The Case of the International Atomic Energy Agency's Technical Cooperation. - GETMANSKY, ANNA. (International Studies Quarterly, 2017)
How and on what grounds do international organizations allocate aid to their member states? I answer this question in the context of the International Atomic Energy Agency (IAEA). I find that political considerations affect the likelihood of receiving aid, as well as the amount of aid that countries receive. In particular, membership in the IAEA board of governors and the acceptance of tougher IAEA inspections increase the likelihood of IAEA assistance. These factors also increase the amounts of assistance, but only for countries with divergent policy preferences from those of the United States. In consequence, those states that receive IAEA assistance are not always those most in need of it. My findings track with theories that countries receive foreign aid in exchange for cooperation and concessions to donors.